Erkki Huttunen liikelaitosten ja yhteisöjen arkkitehtina 1928-1939 - Jokinen, Teppo (1992)
The aim of the study reported here was to survey and analyse the architectural production of Erkki Huttunen (1901-1956), starting from the commencement of his career in 1928 to his later works of 1939. No previous survey of his work is available in any detail, which is why a full list of his work is included in this study. Erkki Huttunen's commissions were generally from business companies and public organizations, the most important being the Finnish Central Cooperative (SOK) and the Finnish Alcohol Monopoly (Aiko). The commissions and the expectations relating to these are presented. This background information is then used as the basis for description and analysis of the design principles of his production. The findings show that Huttunen's early works reflected the prevailing classicist movement of the 1920' s in Finland. In 1930 a transitional period may be observed which follows the model of the Modem Movement in European architecture. Huttunen made a specific effort to use structures made of reinforced concrete. Simultaneous to the pursuit of finding construction solutions, he also aimed at creating aesthetic forms and establishing a harmonious balance between the different parts of a building. Many of Huttunen's designs are classified as masterpieces of 1930's Finnish architecture, and his influence in spreading the Modem Movement in Finland is recognised as particularly significant.